INTERNATIONAL LINKAGES TO THE INDONESIAN CAPITAL MARKET : COINTEGRATION TEST - Abimanyu, Yoopi; Warsidi, Nur Sigit; Kartiko, Sunu; Kurnia, Ridiani; Mahrani, Tety (Jurnal Kajian Ekonomi dan Keuangan, 2012)
This paper explores the international linkages of the Indonesian capital market using cointegration tests to examine the long-run equilibrium relationship between the stock markets of Indonesia with China, France, Germany, Hong Kong, Japan, Korea, Malaysia, Netherlands, Philippine, Singapore, Thailand, Taiwan, the United Kingdom, and the United States. The method used in this paper is visual inspection, followed by Johansen cointegration. Our results show that there exist cointegration between these stock market indices except between Indonesia and Philippine.